Structural Model for the Spider Silk Protein Spidroin-1 - Aparecido dos Santos-Pinto, Jose Roberto [UNESP]; Arcuri, Helen Andrade [UNESP]; Priewalder, Helga; Salles, Heliana Clara [UNESP]; Palma, Mario Sergio [UNESP]; Lubec, Gert (Amer Chemical Soc, 2015)
Most reports about the 3-D structure of spidroin-1 have been proposed for the protein in solid state or for individual domains of these proteins. A gel-based mass spectrometry strategy using collision-induced dissociation (CID) and electron-transfer dissociation (ETD) fragmentation methods was used to completely sequence spidroins-1A and -1B and to assign a series of post-translational modifications (PTMs) on to the spidroin sequences. A total of 15 and 16 phosphorylation sites were detected on spidroin-1A and -1B, respectively. In this work, we present the nearly complete amino acid sequence of spidroin-1A and -1B, including the nonrepetitive N- and C-terminal domains and a highly repetitive central core. We also described a fatty acid layer surrounding the protein fibers and PTMs in the sequences of spidroin-1A and -1B, including phosphorylation. Thus, molecular models for phosphorylated spidroins were proposed in the presence of a mixture fatty acids/water (1:1) and submitted to molecular dynamics simulation. The resulting models presented high content of coils, a higher percentage of alpha-helix, and an almost neglected content of 3(10)-helix than the previous models. Knowledge of the complete structure of spidroins-1A and -1B would help to explain the mechanical features of silk fibers. The results of the current investigation provide a foundation for biophysical studies of the mechanoelastic properties of web-silk proteins.
Keywords: silk proteins; Nephila clavipes; mass spectrometry; post-translational modification; molecular dynamics